2020
DOI: 10.1177/1071100720931085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abnormal Ultrasound Findings in Asymptomatic Posterior Tibial Tendons

Abstract: Background: Posterior tibial tendon dysfunction (PTTD) is a pathological condition that can cause failure of the posterior tibial tendon (PTT). Initially, patients with PTTD are often asymptomatic, making early identification and treatment challenging. Certain ultrasound (US) characteristics have been implicated in the presence of tendinopathy, but their frequency has yet to be assessed in the PTT. The purpose of this study was to identify and report on the frequency of incidental, or potentially early subclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…A similar study, which shared participants with the current study, focused on identifying the prevalence of US findings in posterior tibial tendons (PTTs). 14 Increased BMI was a significant risk factor for the prevalence of abnormal US findings of PTTs in African American participants, which is different from the findings of this study of the peroneal tendons. Also in this study, Caucasian participants were found to have almost 3 times higher odds of having abnormal US findings of the PTT.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar study, which shared participants with the current study, focused on identifying the prevalence of US findings in posterior tibial tendons (PTTs). 14 Increased BMI was a significant risk factor for the prevalence of abnormal US findings of PTTs in African American participants, which is different from the findings of this study of the peroneal tendons. Also in this study, Caucasian participants were found to have almost 3 times higher odds of having abnormal US findings of the PTT.…”
Section: Discussioncontrasting
confidence: 99%
“…35 A recent study found that 67% of participants, and almost half (48.1%) of tibialis posterior tendons, evaluated by ultrasound examination had changes considered to be tendinopathy, despite participants not having medial foot/ankle pain. 22 Even though the link U OBJECTIVE: To determine the reliability of common clinical tests for tibialis posterior tendinopathy (TPT) and to investigate their relationship with grayscale ultrasound findings in individuals who have medial foot/ankle pain.…”
mentioning
confidence: 99%
“…The existence of ethnic differences in foot muscles has been suggested in several papers [ 4 , 19 ]. Caucasian individuals were found to be nearly three times more likely to show tendinopathic findings when compared to African American individuals according to a study using ultrasound [ 20 ]. Additionally, a previous study suggested high morphological variability of the TPT in relation to the insertion location, along with the possibility of significant differences according to ethnic group and gender [ 8 ].…”
Section: Discussionmentioning
confidence: 99%